2017
DOI: 10.1186/s12891-017-1405-8
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the 12-item Oxford knee score for use in Finland

Abstract: BackgroundThe focus in the reporting of results after total knee replacement (TKR) has changed from surgeon/radiologist-based scores to patient-reported outcome measures (PROMs). The questionnaires used in subjective outcome are often originally published in English and need to be validated in different languages. The aim of our study was to investigate the feasibility, validity, reliability, and responsiveness of the Finnish language version of the Oxford Knee Score (OKS-S) questionnaire.MethodsThe original O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…Discriminatory or known-groups validity seems adequate since the outcome score differs greatly in subjects with very different scores on the WOMAC or the EQ-5D-5 L scales. Additionally, it does not show significant ceiling or floor effects that compromise such discriminatory capacity, as has been previously pointed out in other adaptations [ 17 , 20 , 21 , 29 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Discriminatory or known-groups validity seems adequate since the outcome score differs greatly in subjects with very different scores on the WOMAC or the EQ-5D-5 L scales. Additionally, it does not show significant ceiling or floor effects that compromise such discriminatory capacity, as has been previously pointed out in other adaptations [ 17 , 20 , 21 , 29 ].…”
Section: Discussionsupporting
confidence: 71%
“…Although the OKS has been adapted to Spanish for Spain, its psychometric properties have not been assessed in the Spanish population setting. As far as we know, only the Dutch and Finnish language adaptations of OKS have been validated in a prospective manner, similarly to the original work by Dawson et al [ 18 , 29 ], whereas its factor structure has not been confirmed in any of its adapted versions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect to be considered is the possibility of treating predictive variables as continuous or ordinal. Responses to OKS/OHS questionnaires are usually made using Likert scales [42,43,45,46]. Instruments that use Likert-type responses provide a categorical description of an underlying continuous variable.…”
Section: Discussionmentioning
confidence: 99%
“…The osteoarthritis in each knee was radiographically quantified using the Kellgren Lawrence classification 9 . Their knee range of motion was measured 17 . The mechanical axis was measured from standard weight-bearing alignment X-rays.…”
Section: Measurementsmentioning
confidence: 99%